1994
DOI: 10.1007/bf00184116
|View full text |Cite
|
Sign up to set email alerts
|

Specific binding of bacillus Calmette-Gu�rin to urothelial tumor cells in vitro

Abstract: Intravesical immunotherapy with bacillus Calmette-Guérin (BCG) against recurrences of superficial bladder cancer and carcinoma in situ is a highly effective regimen in urology. Despite intensive efforts to clarify the immunological mechanisms of the most successful immunotherapy known today, the cellular mechanism of its antitumor activity remains unknown. In our approach to elucidate the way of action of intravesical BCG, we applied an in vitro adhesion assay to investigate the interaction of radiolabeled BCG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…Our patient population is not large enough to draw certain results but this observation suggests that the binding of BCG to bladder tumor cells is not influenced by soluble fibronectin. In confirmation of this finding, Schneider et al [17] have shown that in vitro interaction of radiolabeled BCG with urothelial tumor cells was not effected by soluble FN.…”
Section: Discussionsupporting
confidence: 56%
“…Our patient population is not large enough to draw certain results but this observation suggests that the binding of BCG to bladder tumor cells is not influenced by soluble fibronectin. In confirmation of this finding, Schneider et al [17] have shown that in vitro interaction of radiolabeled BCG with urothelial tumor cells was not effected by soluble FN.…”
Section: Discussionsupporting
confidence: 56%
“…Thus, sTn may contribute to a more efficient binding of the bacillus to tumour cells and consequently a better response to BCG. The bacillus may also directly target cells in a fibronectin-independent manner (Schneider et al , 1994), namely by binding sTn or specific carbohydrates residues such as α 2,6 sialic acids. On the other hand, sTn is a product of incomplete O -glycosylation of proteins (Dall'Olio et al , 2012), a reduction in the structural complexity of O -glycan may allow the bacillus to bind more efficiently to tumour cells.…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment of T24 cells, a human TCC cell line, with anti-FN or anti-a5b1-receptor antibodies resulted in an impaired BCG attachment to and internalisation in these cells. However, other investigators could not inhibit BCG internalisation with anti-FN antibodies (Schneider et al, 1994;Bevers et al, 2000). The current available data do not suggest a mandatory role of FN in BCG internalisation.…”
Section: Internalisation Of Bcg and Phenotypical Alterations Of Urothmentioning
confidence: 96%
“…The current available data do not suggest a mandatory role of FN in BCG internalisation. It seems that BCG internalisation is mediated by additional molecule(s), possibly coexpressed with FN, such as heparan sulphate-containing proteoglycans interacting with the mycobacterial heparin-binding haemagglutinin adhesin (HBHA) (Schneider et al, 1994;Bevers et al, 2000).…”
Section: Internalisation Of Bcg and Phenotypical Alterations Of Urothmentioning
confidence: 99%